2013
DOI: 10.1371/journal.pone.0074201
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Na+/H+ Exchanger Isoform 1 Promotes Microglial Migration

Abstract: Regulation of microglial migration is not well understood. In this study, we proposed that Na+/H+ exchanger isoform 1 (NHE-1) is important in microglial migration. NHE-1 protein was co-localized with cytoskeletal protein ezrin in lamellipodia of microglia and maintained its more alkaline intracellular pH (pHi). Chemoattractant bradykinin (BK) stimulated microglial migration by increasing lamellipodial area and protrusion rate, but reducing lamellipodial persistence time. Interestingly, blocking NHE-1 activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
(65 reference statements)
1
28
0
Order By: Relevance
“…1), indicating that this TAC-effect is a transient phenomenon. This transient effect may also account for the seeming paradox that TAC stimulates the sodium hydrogen exchangers which is known to participate in the machinery accomplishing cell migration [40] and yet inhibits cell migration as previously reported [7]. According to previous studies [41] [7,8].…”
Section: Discussionmentioning
confidence: 68%
“…1), indicating that this TAC-effect is a transient phenomenon. This transient effect may also account for the seeming paradox that TAC stimulates the sodium hydrogen exchangers which is known to participate in the machinery accomplishing cell migration [40] and yet inhibits cell migration as previously reported [7]. According to previous studies [41] [7,8].…”
Section: Discussionmentioning
confidence: 68%
“…Recent studies suggested that NHE activity and normalized pH are required in the migration of various cells. Stimulation of NHE-1 promotes microglial migration via Na + and Ca 2+ signaling [22]; increased NHE activity contributes to proliferation and migration of smooth muscle cells in the model of pulmonary arterial hypertension [23]. Of interest, the results showed that sNHE expression is positively correlated with motility parameters.…”
Section: Discussionmentioning
confidence: 98%
“…Colocalization of NHE1 and ezrin was analyzed using Image J software with the Colocalization Indices plugin (50). The Pearson's correlation coefficient and overlap coefficient were used as indices of the frequency of colocalization between NHE1 and ezrin as described previously (16). Pearson correlation coefficient was calculated using online statistics software (http://www.wessa.net/, Free Statistics Software, Office for Research Development and Education, version 1.1.23-r7).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were excited every 20 s at 440 and 490 nm, and the emission fluorescence at 535 nm was recorded (16). The ratio of the background-corrected fluorescence emissions (F 490 /F 440 ) was calibrated using the high-K + /nigericin technique (17).…”
Section: Nhe1 In Gbmmentioning
confidence: 99%
See 1 more Smart Citation